Composição químico-bromatológica da silagem de milho cultivado nos sistemas de plantio direto e convencional sob efeito de veranico e da colheita de espigas verdes - Carvalho, Donato Ribeiro de (Universidade Federal Rural do Semi-Árido, 2015)
Two experiments were conducted in order to evaluate the effect of dry spells period on the chemical-bromatologic composition of corn (Zea mays L.) silage and evaluate the chemical-bromatologic composition of corn silage without corn on the cob, collected for marketing as green corn, grown in the till and conventional tillage systems. The characteristics evaluated in both experiments were: dry matter yield, percentage of dry matter and the chemical analysis, the following characteristics were evaluated: pH, crude protein, ether extract, cellulose, hemicellulose, lignin, ash, crude energy, nitrogen neutral detergent insoluble nitrogen, acid detergent, neutral detergent fiber and acid detergent fiber For the first experiment, we used a split-plot, distributed in a randomized block design with four replications. In the plots we evaluated two tillage systems (direct and conventional) and the subplots six periods of dry spells (2.6, 10, 14, 18 and 22 days) and it was found that the increase of Indian summer period affected the chemical-bromatologic composition of silage in both planting systems, however, the no-tillage system reduces the loss of silage chemical-bromatologic composition by water deficit in comparison to conventional tillage. The second experiment, the schedule showed the subdivided parcels, distributed in a randomized block design with eight replications. In the plots we evaluated the two planting systems (direct and conventional) and the plots, plants with and without ears and it was found that the removal of the damaged ear silage chemical-bromatologic composition and best dry matter production rates and chemical-bromatologic composition silage were checked in no-tillage system
chemical-bromatologic composition of cultivated corn silage in the tillage and conventional tillage systems under veranico effect and harvesting green ears
Keywords: Zea mays L .; Corn silage; Bromatological analysis; Zea mays L.; Silagem de milho; Análise bromatológica; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO